Estudio comparativo sobre las herramientas de lenguaje de programación java y Python en el desarrollo de aplicaciones Android. - Villacrés Tandazo, Hilda Stefany (2022)
The development of Android applications in today's technology and programming have become very common, to understand how to configure or design Android mobile devices, you should know that these mobile devices have been designed in Java for many years, as it is one of the most popular programming languages in the world, as it is a cross-platform language, Its simplicity and robustness when creating applications makes it one of the most powerful languages today, and through much research, there is another developer that is known as Python is another successful language, although Android does not support the development of Python natively, cross-platform mobile applications can be created using platforms such as Kivy. The objective of this comparative study of these languages is to conduct a series of investigations on Java and Python programming language tools, with these systems for Android application development, detect which of these systems is more cost-effective or feasible to run a mobile device to enable seamless mobile operation and performance. Java's strength is that it includes documentation for users who are new to programming, as well as many professional tutorials. It is also described as a cross-platform object-oriented language that allows for modularization, greater support for mobile application development, and an interpreted language, making it very easy to learn. There are many frameworks that make development easier and faster. Generally, Python is a general-purpose dynamically typed programming language, which has less code, is easy to use, and is simpler to learn, although it does work with some programs or applications that are popular, it is not as extensive as Java has worked.